Medical results of preparticipation examination in adolescent athletes. Issue 7 (10th May 2012) - Mayer, Frank; Bonaventura, Klaus; Cassel, Michael; Mueller, Steffen; Weber, Josefine; Scharhag-Rosenberger, Friederike; Carlsohn, Anja; Baur, Heiner; Scharhag, Juergen
Abstract : Background: Preparticipation examinations (PPE) are frequently used to evaluate eligibility for competitive sports in adolescent athletes. Nevertheless, the effectiveness of these examinations is under debate since costs are high and its validity is discussed controversial. Purpose: To analyse medical findings and consequences in adolescent athletes prior to admission to a sports school. Methods: In 733 adolescent athletes (318 girls, 415 boys, age 12.3±0.4, 16 sports disciplines), history and clinical examination (musculoskeletal, cardiovascular, general medicine) was performed to evaluate eligibility. PPE was completed by determination of blood parameters, ECG at rest and during ergometry, echocardiography and x-rays and ultrasonography if indicated. Eligibility was either approved or rated with restriction. Recommendations for therapy and/or prevention were given to the athletes and their parents. Results: Historical (h) and clinical (c) findings (eg, pain, verified pathologies) were more frequent regarding the musculoskeletal system (h:120, 16.4%; c:247, 33.7%) compared to cardiovascular (h:9, 1.2%; c:23, 3.1%) or general medicine findings (h:116, 15.8%; c:71, 9.7%). ECG at rest was moderately abnormal in 46 (6.3%) and severely abnormal in 25 athletes (3.4%). Exercise ECG was suspicious in 25 athletes (3.4%). Relevant echocardiographic abnormalities were found in 17 athletes (2.3%). In 52 of 358 cases (14.5%), x-rays led to diagnosis (eg, Spondylolisthesis). Eligibility was temporarily restricted in 41 athletes (5.6%). Three athletes (0.4%) had to be excluded from competitive sports. Therapy (eg, physiotherapy, medication) and/or prevention (sensorimotor training, vaccination) recommendations were deduced due to musculoskeletal (t:n=76, 10.3%;p: n=71, 9.8%) and general medicine findings (t:n=80, 10.9%; p:n=104, 14.1%). Conclusion: Eligibility for competitive sports is restricted in only 5.5% of adolescent athletes at age 12. Eligibility refusals are rare. However, recommendations for therapy and prevention are frequent, mainly regarding the musculoskeletal system. In spite of time and cost consumption, adolescent preparticipation before entering a career in high-performance sports is supported.